The Impact of Yoga on Self-Regulation Skills in 60-69 Month-Old Children Attending Preschool Education - Seven, Vera; Kaya, İsa (Kızıl & Irmak Yayınları, 2025)
This study investigates the impact of a yoga training program on the self-regulation skills of children aged 60 to 69 months who are enrolled in preschool education. The research utilizes a quasi-experimental design featuring pre-test and post-test control groups within a quantitative research framework. The participants of the study consist of a total of 36 children, including 13 boys and 23 girls, all aged between 60-69 months and enrolled in preschool classes. The selection of participants was made using a purposive sampling method. To obtain participation consent for the children involved in the study, an “Informed Consent Form” was presented to their families, and demographic information of the children and their families was gathered using a “Personal Information Form”. The “Self-Regulation Skills Scale for 4-6 Year-Old Children (Teacher Form)”, developed by İvrendi and Erol (2018), was employed to assess the self-regulation abilities of both the experimental and control groups.The scale has an internal consistency coefficient of 0.94 and a test-retest reliability coefficient of 0.81. The overall Cronbach’s Alpha value of the scale is 0.96. For the analysis of the data, statistical software was utilized, and the pre-test and post-test data were analyzed using the t-test. The findings of the research indicate significant differences between the pre-test and post-test average scores of the experimental group in the sub-dimensions of inhibitory control, attention, and working memory related to self-regulation. Based on these results, it can be concluded that yoga has a positive impact on the development of children’s self-regulation skills. Thus, it is suggested that yoga can be integrated into educational programs as an alternative method.

Bu çalışma, okul öncesi eğitime devam eden 60-69 ay arasındaki çocukların öz-düzenleme becerileri üzerindeki yoga eğitim programının etkisini araştırmaktadır. Araştırma, nicel araştırma çerçevesinde ön test-son test kontrol gruplu yarı deneysel bir desen kullanmaktadır. Çalışmanın katılımcıları, 60-69 ay yaş aralığında olup okul öncesi sınıflarına devam eden 13’ü erkek, 23’ü kız olmak üzere toplam 36 çocuktan oluşmaktadır. Katılımcılar amaçlı örnekleme yöntemiyle seçilmiştir. Araştırmaya katılan çocukların ebeveynlerinden izin almak amacıyla “Bilgilendirilmiş Onam Formu” sunulmuş, çocuklar ve ailelerine ait demografik bilgiler “Kişisel Bilgi Formu” ile toplanmıştır. Deney ve kontrol gruplarındaki çocukların öz-düzenleme becerilerini değerlendirmek için İvrendi ve Erol (2018) tarafından geliştirilen “4-6 Yaş Çocukları İçin Öz-Düzenleme Becerileri Ölçeği (Öğretmen Formu)” kullanılmıştır. Ölçeğin iç tutarlık katsayısı 0.94, test-tekrar test güvenirlik katsayısı ise 0.81 olarak belirlenmiştir. Ölçeğin genel Cronbach’s Alpha değeri 0.96’dır. Verilerin analizi için istatistiksel yazılım kullanılmış ve ön test-son test verileri t-testi ile analiz edilmiştir. Araştırma bulguları, deney grubunun ön test ve son test ortalama puanları arasında öz-düzenleme ile ilişkili olan engelleyici kontrol, dikkat ve çalışma belleği alt boyutlarında anlamlı farklar olduğunu göstermektedir. Bu sonuçlara dayanarak yoganın çocukların öz-düzenleme becerilerinin gelişimi üzerinde olumlu bir etkisi olduğu sonucuna varılmıştır. Bu nedenle, yoga uygulamalarının eğitim programlarına alternatif bir yöntem olarak entegre edilmesi önerilmektedir.
Okul Öncesi Eğitimde 60-69 Aylık Çocukların Öz-Düzenleme Becerileri Üzerinde Yoga’nın Etkisi
Keywords: Educational Program; Preschool Period; Self-regulation; Yoga; Eğitim Programı; Okul Öncesi Dönemi; Öz-düzenleme; Yoga